2007
DOI: 10.1534/genetics.107.075051
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Gives Rise to Different Isoforms of the Neurospora crassa Tob55 Protein That Vary in Their Ability to Insert β-Barrel Proteins Into the Outer Mitochondrial Membrane

Abstract: Tob55 is the major component of the TOB complex, which is found in the outer membrane of mitochondria. A sheltered knockout of the tob55 gene was developed in Neurospora crassa. When grown under conditions that reduce the levels of the Tob55 protein, the strain exhibited a reduced growth rate and mitochondria isolated from these cells were deficient in their ability to import b-barrel proteins. Surprisingly, Western blots of wild-type mitochondrial proteins revealed two bands for Tob55 that differed by $4 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 62 publications
5
23
0
Order By: Relevance
“…We previously suggested that N. crassa Mdm10 has a general effect on TOB complex function [26]. Interestingly, our model fits with certain aspects of the one described above since N. crassa strains lacking Mdm10 do have a porin assembly defect [26] and a stable intermediate for porin assembly can be detected in N. crassa [36]. A third model suggests that the role of Mdm10 is to assist the TOB complex with the assembly of Tom22 [29], [30].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We previously suggested that N. crassa Mdm10 has a general effect on TOB complex function [26]. Interestingly, our model fits with certain aspects of the one described above since N. crassa strains lacking Mdm10 do have a porin assembly defect [26] and a stable intermediate for porin assembly can be detected in N. crassa [36]. A third model suggests that the role of Mdm10 is to assist the TOB complex with the assembly of Tom22 [29], [30].…”
Section: Discussionsupporting
confidence: 79%
“…Strains were grown at 30°C unless otherwise noted. General handling procedures for N. crassa [35] and growth tests using sorbose containing medium to force colonial growth were as described previously [36]. The deletion strains used in this study ( Δmmm1 , Δmmm2 , and Δgem1) were developed by the N. crassa gene knockout project [37].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, many cases of alternative splicing have been observed. As examples, alternative splicing was observed in the Chlorella sorokiniana nadp-gdh gene (Miller et al, 1998); S. cerevisiae YKL186C/MTR2 and YML034W genes (Davis et al, 2000); Pneumocystis carinii impdh gene (Ye et al, 2001); Mucor circinelloides rce1 gene (Baba et al, 2005); N. crassa tob55 gene (Hoppins et al, 2007) and N. crassa hex-1 gene (Leal et al, 2009). In all the cited works, intron retention rather than the formation of exon cassettes seems to be the prevalent alternative splicing event in fungi (McGuire et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The first heterokaryon (RIP40het) was isolated (19) using the technique of sheltered RIP (repeat-induced point mutation). The second (Tom40 KO-5) was developed by the method of sheltered disruption in heterokaryon HP1 as described previously for mutants of Tob55 (42). The nuclei of the heterokaryons can be differentiated and selected using differing auxotrophic and drug-resistance markers.…”
Section: Methodsmentioning
confidence: 99%